Maintaining a Hopeless Traumatized Maxillary Central Incisor as a Transient Treatment Option: A Case Report with a 3-Years Follow-Up - Ghahramani, Yasamin; Moazami, Fariborz; Samadi, Yasser; eskandari, fateme (Iranian Endodontic Journal, 2022)
An open apices tooth is among the rare types of traumatic dental injuries is horizontal root fracture. Many factors may affect the treatment and prognosis of root fractures, like the time between trauma and treatment, degree of dislocation and mobility, stage of tooth development, fracture site, and patient’s age. This case presents a horizontal root fracture of a maxillary central incisor in an 8-year-old boy. The tooth was considered for extraction due to excessive mobility and deep probing depth, but the patient’s parents refused to extract the tooth. After one year, during the follow-up examination, we noticed an unprecedented healing process had been initiated. Due to the weak crown-to-root ratio, the traumatized tooth was splinted to the surrounding teeth to reduce the wrecking forces and promote healing. In a three-year follow-up, the cone-beam computed tomography examination showed that the coronal and apical fragments continued to develop separately. Also, it was observed that the mobility and probing depth were reduced significantly.